1976
DOI: 10.1002/bip.1976.360150508
|View full text |Cite
|
Sign up to set email alerts
|

Konformationsuntersuchungen an oligoalanin, substanz P und der myoglobinsequenz (66–73) der zirkulardichroismus von polyäthylenglykolgebundenen peptiden

Abstract: SynopsisThe conformation of polyethylene glycol-bound peptides, synthesized by the liquidphase method, was investigated. This marcromolecular C-terminal protecting group is transparent in the visible and the ultraviolet range to 190 nm and solubilizes peptides in many different solvents. The CD spectra of the polymer-bound myoglobin sequence 66-73 and of the biologically active undecapeptide "substance P" were measured in each step of the synthesis. In both examples the formation of a secondary structure durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
3

Year Published

1979
1979
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 24 publications
1
14
0
3
Order By: Relevance
“…It is interesting to note that the concept of using small solubilizing groups rather than DL ‐polypeptides evolved from a desire to perturb the structure as little as possible. Later studies using polyethylene glycol to solubilize nona‐ and deca‐alanine completely confirmed these results,18 and strikingly, a 16‐mer containing 13 alanine residues and 3 lysine residues for solubility purposes assumed a helical structure at 1°C in water 10. Thus one could argue that the early work on protected oligoalanines in organic fluoroalcohols correctly indicated the conformational preference of this amino acid and provided insights into the chain‐length dependence of its helix formation.…”
Section: Part I: Retrospective and Backgroundmentioning
confidence: 88%
“…It is interesting to note that the concept of using small solubilizing groups rather than DL ‐polypeptides evolved from a desire to perturb the structure as little as possible. Later studies using polyethylene glycol to solubilize nona‐ and deca‐alanine completely confirmed these results,18 and strikingly, a 16‐mer containing 13 alanine residues and 3 lysine residues for solubility purposes assumed a helical structure at 1°C in water 10. Thus one could argue that the early work on protected oligoalanines in organic fluoroalcohols correctly indicated the conformational preference of this amino acid and provided insights into the chain‐length dependence of its helix formation.…”
Section: Part I: Retrospective and Backgroundmentioning
confidence: 88%
“…Während sich die Anwesenheit der Benzylschutzgruppen nur unwesentlich auf das CD-Spektrum auswirkt, läßt sich beim Übergang vom Nonazum Dekapeptid eine deutliche Erhöhung der Elliptizität bei ~ 230 nm feststellen, was eine Zunahme an Sekundärstruktur anzeigt. Die Berechnung des prozentualen Anteils der experimentellen Kurven an Sekundärstruktur mit verschiedenen Auswertungsmethoden [23][24][25] Alle drei Kurven zeigen den für eine ^-Struktur typischen negativen Cottoneffekt bei 218 nm (n-n*-Übergang) sowie einen starken positiven Cotton- [7,26]. Während das N-ungeschützte Nonapeptid (III) praktisch reine random-coil-Struktur besitzt, deutet die starke Zunahme des negativen Cottoneffekts bei 222 nm (ft-7r*-Übergang) auf das Vorliegen helikaler Anteile im N-^-Boc-geschützten Peptid (II) hin; die Bedeutung des Aminoendes für die Stabilität der Sekundärstruktur tritt hier besonders deutlich hervor und wurde auch bei Homooligopeptiden beobachtet [7,12].…”
Section: Cd-messungenunclassified
“…Die Vorhersagen werden anhand von CD-Untersuchungen an synthetischen ACTH-analogen Segmenten überprüft. Zur Synthese der zum Teil schwerlöslichen Segmente wird die LiquidPhase Methode [5,6] verwendet, die sich wegen der Anwesenheit einer makromolekularen, solubilisierenden Schutzgruppe vor allem für die Synthese von Oligopeptiden im Zusammenhang mit Konformationsuntersuchungen in organischem und wäßrigem Medium bewährt hat [7][8][9][10][11][12]. Konformationsuntersuchungen an PEG-gebundenen Oligopeptiden eröffnen grundsätzlich neue Möglichkeiten, da (i) durch den rationellen stufenweisen Aufbau der Peptidkette nach der Liquid-Phase-Methode der Einfluß von Primärsequenz, Kettenlänge, Schutzgruppen, Lösungsmittel etc.…”
unclassified
See 1 more Smart Citation
“…12 Polyethylene glycol (PEG) chains have been shown to possess b-sheet disintegrating properties. 13 When PEG is attached to the solid phase, the efficiency of a solid phase synthesis improves significantly as long as the growing peptide chain is close (closer than 15 amino acid residues) to the polyethylene glycolcontaining matrix.PEG also increases the solubility of the moieties attached. PEG had been introduced previously as a solubilizing C-and N-terminal protecting group of carrier-bound peptides in SPPS.…”
mentioning
confidence: 99%